2010
DOI: 10.1519/jsc.0b013e3181e7ff9a
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Functional Isometric Squats on Vertical Jump in Trained and Untrained Men

Abstract: Functional isometrics (FIs) combine dynamic and isometric muscle actions and may hyperstimulate the nervous system leading to an enhanced postactivation potentiation (PAP) and improved subsequent performance. The purpose of this study was to investigate the impact of an FI squat on the countermovement vertical jump (CMVJ) in resistance trained and untrained men. Thirteen trained men (age: 22.8 +/- 3.2 years, mass: 90.0 +/- 16.3 kg, and height: 178.9 +/- 7.1 cm) and 8 untrained men (age: 28.5 +/- 5.9 years, mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
23
2
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 18 publications
5
23
2
2
Order By: Relevance
“…PAP is known to significantly enhance muscular power assessed through isokinetic contractions [2], jumps [2, 3, 5], and other athletic activities [11]. However, in the present study, a previous MVC led to 3.5% increases in IPT of a second MVC performed 180 seconds later.…”
Section: Discussioncontrasting
confidence: 66%
“…PAP is known to significantly enhance muscular power assessed through isokinetic contractions [2], jumps [2, 3, 5], and other athletic activities [11]. However, in the present study, a previous MVC led to 3.5% increases in IPT of a second MVC performed 180 seconds later.…”
Section: Discussioncontrasting
confidence: 66%
“…The improvement in the Prowler and 18.2 meter sprint times as a result of the BSQ PAP warmup found in this study is consistent with prior studies which have demonstrated that a PAP warmup can significantly increase both upper and lower body power output [10][11][12][13][14][15]. Fourteen of the participants experienced an improvement in sled push times while the others experienced no change or a slower time as the result of the PAP warmup.…”
Section: Discussionsupporting
confidence: 90%
“…The present study used recreationally trained individuals to investigate lower body isometric strength after various warm-up protocols. Berning et al (2010), reported that a general warm-up (5-minutes of cycling) in conjunction with one, 3-second heavy isometric squat (150% of the participants 1RM) elicited greater vertical jump height in recreationally trained individuals indicating that a supramaximal isometric muscle action enhances performance. This suggests the isometric intensity utilized in the present study may not have been great enough to elicit increased strength.…”
Section: Discussionmentioning
confidence: 99%